The Strengthening of Fisherwomen Livelihoods in Benan Island Village Through Village Tourism Institutions - Khodijah Ismail (Lasigo Akademia Indonesia, 2023)
This study aims to analyze the involvement of fisherwomen in managing tourism villages and the relationship between actors involved in tourism management. The researcher chose Benan Island as the research location, one of the small islands in Lingga Regency, Indonesia. This study uses a qualitative descriptive approach, and the interpretation of the results of data analysis uses spidergram images according to the priority scale. Data collection uses the method of study documentation, observation, Focus Group Discussion, and in-depth interviews. The study results show that fisherwomen's level of involvement in village tourism management still needs to be higher. The management of tourism in the village has a top-down pattern. Namely, the district government assigns village tourism management personnel. Such a management system makes it difficult for the women's community to participate actively.